2014
DOI: 10.5194/se-5-1169-2014
|View full text |Cite
|
Sign up to set email alerts
|

Wave-equation-based travel-time seismic tomography – Part 2: Application to the 1992 Landers earthquake (<i>M</i><sub>w</sub> 7.3) area

Abstract: Abstract. High-resolution 3-D P and S wave crustal velocity and Poisson's ratio models of the 1992 Landers earthquake (Mw 7.3) area are determined iteratively by a wave-equation-based travel-time seismic tomography (WETST) technique. The details of data selection, synthetic arrival-time determination, and trade-off analysis of damping and smoothing parameters are presented to show the performance of this new tomographic inversion method. A total of 78 523 P wave and 46 999 S wave high-quality arrival-time data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 56 publications
3
15
0
Order By: Relevance
“…Tens of thousands of earthquakes have been recorded by the Southern California Seismic Network (SCSN), which provides us abundant data to explore the seismic structures of this region. Following the pioneering seismic tomography work of Aki and Lee [], many studies have been conducted to explore the subsurface structure in Southern California [e.g., Dziewonski et al , ; Zhao and Kanamori , ; Zhao et al , ; Tape et al , , ], revealing structural heterogeneities in the crust and upper mantle of this region [e.g., Lin et al , ; Tape et al , ; Tong et al , ]. The results provided by Tong et al [] are consistent with the other studies, indicating the validity of the WETST method in real applications.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Tens of thousands of earthquakes have been recorded by the Southern California Seismic Network (SCSN), which provides us abundant data to explore the seismic structures of this region. Following the pioneering seismic tomography work of Aki and Lee [], many studies have been conducted to explore the subsurface structure in Southern California [e.g., Dziewonski et al , ; Zhao and Kanamori , ; Zhao et al , ; Tape et al , , ], revealing structural heterogeneities in the crust and upper mantle of this region [e.g., Lin et al , ; Tape et al , ; Tong et al , ]. The results provided by Tong et al [] are consistent with the other studies, indicating the validity of the WETST method in real applications.…”
Section: Introductionmentioning
confidence: 53%
“…Table shows quantitatively the structural similarity (SSIM) indices defined by Tong et al [] between the recovered P or S velocity models and the input checkerboard models at seven layers. As discussed in Tong et al [], the inverted model is better recovered when the SSIM index is close to 1.0. It can be observed that the SSIM indices are above 0.75 at the depths less than 21.0 km regardless of whether Moho‐reflected phases are used or not.…”
Section: Resolution Testsmentioning
confidence: 91%
See 3 more Smart Citations